Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/pmic.200600212
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic knowledge of human aquaporins

Abstract: Aquaporins (AQPs) are an ubiquitous family of proteins characterized by sequence similarity and the presence of two NPA (Asp-Pro-Ala) motifs. At present, 13 human AQPs are known and they are divided into two subgroups according to their ability to transport only water molecules (AQP0, AQP1, AQP2, AQP4, AQP5, AQP6, and AQP8), or also glycerol and other small solutes (AQP3, AQP7, AQP9, AQP10, AQP12). The genomic, structural, and functional aspects of this family are briefly described. In particular, proteomic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 134 publications
1
55
0
1
Order By: Relevance
“…They share the same basic architecture with a cytosolic N-and C-terminus and a hydrophobic stretch of six transmembrane domains, connected by three extracellular and two intracellular loops. The transmembrane domains form an hourglass structure with the NPA motifs at the center of the molecule (reviewed in Magni et al (2006)). Several observations of AQP monomers forming a homotetrameric organization in the membrane have been made (Engel et al 2000), and this feature is probably similar for all members of the AQP family.…”
Section: Aqp Protein Familymentioning
confidence: 99%
“…They share the same basic architecture with a cytosolic N-and C-terminus and a hydrophobic stretch of six transmembrane domains, connected by three extracellular and two intracellular loops. The transmembrane domains form an hourglass structure with the NPA motifs at the center of the molecule (reviewed in Magni et al (2006)). Several observations of AQP monomers forming a homotetrameric organization in the membrane have been made (Engel et al 2000), and this feature is probably similar for all members of the AQP family.…”
Section: Aqp Protein Familymentioning
confidence: 99%
“…Since then, 13 members of this membrane protein family have been identified in humans (AQP0-12), which are distributed throughout a wide range of tissues. For example, AQP1 has been shown to be highly expressed in red blood cells, kidney proximal tubule cells and many other tissues (Magni et al, 2006), while AQP11 has been found at low levels in smooth muscle or cells of the immune system (Ishibashi, 2009). A number of studies have also shown that AQPs play a role in various disorders from renal disease to cerebral oedema (Benarroch, 2007, Schrier andCadnapaphornchai, 2003) and even cancer (Yin et al, 2008, Chae et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The classically established role of AQPs in mammalian physiology is in transepithelial fluid transport, as occurs in the urinary concentrating mechanism 3 and glandular fluid secretion. 4,5 Several newer and somewhat unexpected roles of AQPs have been identified, such as in the regulation of brain and corneal water balance, neural signal transduction and glycerol metabolism in skin and fat cells.…”
Section: Introductionmentioning
confidence: 99%